Preparation and flame retardancy of flax fabric/polybenzoxazine laminates. (24th April 2020) - Samyn, Fabienne; Murariu, Oltea; Bonnaud, Leila; Duquesne, Sophie
Summary: Driven by the need to reduce the carbon footprint of materials, natural fibres reinforced composites are increasingly used. Today, their level of maturity allows to consider their applications in fields where high performance such as flame retardancy are required. This article compares the fire retardant properties of flax laminates based on two thermosets resins, a bio‐based polybenzoxazine and a petroleum‐based epoxy, both considered for aeronautical applications. The effect of alkaline and silane surface modifications of the fibres on the properties of the composites was investigated. The treatments of the flax were proven to allow a better impregnation of the fibres by the matrices but at the same time more defects were observed. Regarding the fire behaviour of the composites, no difference of flammability was highlighted between the treated and untreated materials. The burnthrough resistance evaluation was performed using a small‐scale aeronautical test. The better performance of the epoxy‐based composite compare to the polybenzoxazine one was shown whereas charring is favoured for polybenzoxazine. The low deformability of the char formed when polybenzoxazine decomposes leads to the formation of cracks with the subsequent failure of the test.